Law Enforcement of Cyber Terorism in Indonesia - Sri Ayu Astuti (Rechtsidee, 2015)
Cyber terrorism is one of the category of crimes that cross border organized and has been established as an extraordinary crime. This crime is becoming a serious threat to countries in the world. In this regard, the Government's attitude of firmness needed to enforce cyber laws against the freedom development in social media. The development of the immeasurable it in the country of Indonesia required the limitations by doing legal liability over the behavior of law which deviates towards the use of technology tools. Strict law enforcement efforts as a clear attitude to stop actively moving massive terrorism, by enacting the provisions of the law on information and electronic transactions as well as the law of terrorism effectively. How To Cite: Astuti, S. (2015). Law Enforcement of Cyber Terorism in Indonesia. Rechtsidee, 2(2), 157-178. doi:http://dx.doi.org/10.21070/jihr.v2i2.82